Complete Response of Skull Base Inverted Papilloma to Chemotherapy: Case Report. Issue 2 (June 2017) - Kuan, Edward C.; Frederick, John W.; Diaz, Miguel F. Palma; Lim, Dean W.; Suh, Jeffrey D.
Background: Inverted papilloma (IP) is the most common benign sinonasal neoplasm. Endoscopic techniques, improved understanding of pathophysiology, and novel surgical approaches have allowed rhinologists to treat IPs more effectively, with surgery being the mainstay of therapy. Frontal sinus IP poses a challenge for surgical therapy due to complex anatomy and potentially difficult surgical access. Objectives: We reported a unique case of a massive frontal sinus IP that presented with intracranial and orbital extension, with near resolution after chemotherapy. Methods: A retrospective case review of a patient with a frontal sinus IP treated at a tertiary academic medical center. Results: A 75-year-old male patient presented with nasal obstruction, purulent nasal discharge, and a growing left supraorbital mass. Endoscopy demonstrated a mass that filled both frontal and ethmoid sinuses, with orbital invasion. There also was substantial erosion of the posterior table, which measured 1.73 × 1.40 cm. A biopsy specimen demonstrated IP with carcinoma in situ. The patient was deemed unresectable on initial evaluation and, subsequently, underwent chemotherapy (carboplatin and paclitaxel). The tumor had a dramatic response to chemotherapy, and the patient elected for definitive surgery to remove any residual disease. During surgery, only a small focus of IP was found along the superior wall of the frontal sinus. No tumor was found elsewhere, including at the site of skull base erosion. The final pathology was IP without carcinoma in situ or dysplasia. Conclusion: This was the first reported case of chemotherapeutic "debulking" of IP, which facilitated surgical resection, despite substantial intracranial and orbital involvement. Although nearly all IPs can be treated surgically, rare cases, such as unresectable tumors, may benefit from systemic chemotherapy.